The Improvement of Existing Slope Reinforcement System and The Design of Alternative Slope Reinforcements Case Study: Lainea-Awunio Road Section Km 98+050 South Konawe Regency, Southeast Sulawesi Province - Kamila, Nadia; Khoiri, Mohamad; Siagian, Freddy (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
The landslide that occurred on the Lainea-Awunio KM 98+050 national road in South Konawe Regency, Southeast Sulawesi caused a partial collapse on the road and disrupted traffic flow. For this reason, slope rehabilitation has been carried out using the construction of retaining walls. Based on the Geological Map and test results, it was found that the soil at the location has a high soil bearing capacity, but in reality, landslides occur during the rainy season and cracks are found on the slopes, therefore it is necessary to analyze slope stability using a cracked soil approach. In this research, slope stability analysis was analyzed using authentic soil data and with a cracked soil approach, slope stability analysis was analyzed using using the GEO5 auxiliary program and reinforcement planning was calculated using manual calculations. After the analysis, it was discovered that the slope that was initially predicted to be safe (SF>1) turned out to be a collapse (SF<1), and the reinforcement system that had been implemented in the field after being evaluated turned out to be not stable enough and required additional reinforcement. The additional reinforcement is designed using bored piles with a diameter of 1 meter to a depth of 13 meters to increase the safety factor from SF=0,66 to SF=1,60. Meanwhile for slopes without reinforcement bored piles with a diameter of 0,8 meters to a depth of 16 meters was used to increase the safety factor from SF=0,51 to SF=1,65.